Development of Interactive Video to Enhance Students’ Understanding of Physical Bullying at SDN 62 Rontu, Bima City - Nurmala, Nurmala; Lastuti, Sri; Imamsyah, Mirham (Journal of Educational Sciences, 2025)
Physical bullying is a type of violence that involves direct physical contact, such as kicking, pulling hair, pinching, or hitting, which can result in physical injuries and long-term psychological effects on victims. This study aims to develop an interactive learning medium in the form of an anti-bullying video titled Stop bullying to improve students’ understanding of physical bullying at SDN 62 Rontu, Bima City. The development process followed the ADDIE model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The research involved 30 students from Grades I to VI. Instruments used in the study included validation questionnaires from subject matter and media experts, response questionnaires for students and teachers, observation sheets, and pre-test and post-test assessments. The validation results showed high validity, with scores of 93.3% from content experts and 90% from media experts. The practicality assessment resulted in scores of 88.13% from students and 88.3% from teachers. The N-Gain test indicated a 0.71 increase in understanding, categorized as high. These findings suggest that the interactive video is an effective and appropriate educational tool for addressing physical bullying in elementary schools.